2015
DOI: 10.3233/jad-142469
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Hydrated Fullerene C60: Cortical and Hippocampal EEG Interplay in an Amyloid-Infused Rat Model of Alzheimer's Disease

Abstract: We studied the effects of fullerene C60 nanoparticles, namely hydrated fullerene C60 (C60HyFn), on interrelations between EEG frequency spectra from the frontal cortex and the dorsal hippocampus (CA1) on an amyloid-β (Aβ) rat model of Alzheimer's disease (AD). Infusion of Aβ1-42 protein (1.5 μl) into the CA1 region two weeks before EEG testing diminished hippocampal theta (3.8-8.4 Hz) predominance and eliminated cortical beta (12.9-26.2 Hz) predominance observed in baseline EEG of rats infused with saline (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…The design of functional materials for the elaboration of high‐performance supramolecular devices that display specific properties is both a conceptual and synthetic challenge . Within this context, [60]fullerene (C 60 ), an exceptional photophysical and electrochemical unit, generated exciting studies in medicinal (DNA photocleavage, enzyme inhibition, virus inhibition, neuroprotection, antibacterial activity) and materials science (photoactive dyads, triads, polyads, and plastic solar cells). To improve the effectiveness of [60]fullerene‐based devices, materials containing two, three, four, or more C 60 units were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…The design of functional materials for the elaboration of high‐performance supramolecular devices that display specific properties is both a conceptual and synthetic challenge . Within this context, [60]fullerene (C 60 ), an exceptional photophysical and electrochemical unit, generated exciting studies in medicinal (DNA photocleavage, enzyme inhibition, virus inhibition, neuroprotection, antibacterial activity) and materials science (photoactive dyads, triads, polyads, and plastic solar cells). To improve the effectiveness of [60]fullerene‐based devices, materials containing two, three, four, or more C 60 units were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…AMPA receptors have been shown to be involved in potentiation of activation of both alpha-secretase and non-amyloidal path of an amyloid precursor (APP) cleavage, i.e., without formation and accumulation of extremely toxic Аβ1-42 [62]. In our previous study, we have revealed С60HyFn-produced inhibition of intracellular Аβ1-42 deposit formation associated with exogenous fibrillar Аβ25-35 [29] and, supposedly, with its endogenous fullerene-disaggregated form [11]. С60HyFn ability to block both intracellular Аβ1-42 generation and the extracellular glutamate receptors activity [63] reducing Ca 2+ inflow, one of the main sources of Аβ25-35 neurotoxicity [64]).…”
Section: Discussionmentioning
confidence: 97%
“…They both converge on single pyramidal cells of the CA1, but affecting them differently. Interestingly, in AD and in its "amyloid-beta" models, early degenerative changes were revealed in CA1 pyramidal neurons [14], [15], [17], [29], [36]. A primary target of Аβ is the EC which, being the main cortical input for the hippocampus, plays a considerable part in memory formation [3], [8], [14], [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations